Chemical Synthesis, Characterization, and Computational Investigation of Two Schiff Bases Derived From 3-(2-Hydroxyphenyl)-4-amino-4H-1,2,4-triazole-5- thiol and Their Corresponding Oxovanadium(IV) Complexes - Sharma, Bharat Prasad; Adhikari Subin, Jhashanath; Panthi, Khim Prasad; Pandey, Sarvesh Kumar; Ahamad, Akeel; Sharma, Motee Lal (Journal of Nepal Chemical Society, 2023)
A triazole, 2-(4-amino-5-mercapto-4H-1,2,4-triazol-3-yl)phenol, has been prepared from 2-hydroxybenzoic acid by routine multi-step chemical synthesis. It was then used in synthesizing two different Schiff base ligands (L1 and L2). Their respective oxovanadium (IV) complexes (ML1 and ML2) were consequently synthesized and characterized by different experimental techniques like elemental analysis, FTIR spectroscopy, UV-Visible spectroscopy, and EPR spectrometry. The cyclic voltammetry measurements showed the electrochemically stable nature of the complexes. The powder X-ray diffraction patterns revealed the presence of monoclinic crystals with particle sizes of ca. 15-17 nm for both complexes. DFT calculations were performed for the determination of geometrical models, energetic stability, electronic properties, spectral features, and reactivity of the synthesized ligands and complexes. The spectral characterization of the complexes suggests a square-pyramidal geometry around VO (IV)group and was supported by computational results derived from the proposed models. This work shows that computational calculation along with experimental characterization provides better insights into new chemical compounds and their properties that could be performed in parallel as a regular tool.